Expert C# 2005 Business Objects - Lhotka, Rockford (Apress : Imprint: Apress, 2006)
Rockford Lhotka started writing his Business Objects books in 1996, and over the years, he's become one of the world's foremost authorities on building distributed object-oriented systems. His industry-standard VB .NET Business Objects book not only addresses changes in .NET 2.0 and Visual Studio 2005, but also reflects substantial enhancements and improvements to the CSLA .NET Framework and how it can be used to create enterprise-level .NET applications. Expert C# 2005 Business Objects is for developers who want to see Lhotka's ideas applied in the C# idiom. The book takes you from an opening discussion of logical architectures to detailed n-tier deployment options using the CSLA .NET Framework. The depth of Rockford's thinking now influences developers across language boundaries. With this book, you can learn directly from the expert whose framework has become universally accepted and respected.